2020
DOI: 10.3390/cancers12020474
|View full text |Cite
|
Sign up to set email alerts
|

Biological Features and Prognostic Impact of Bone Marrow Infiltration in Patients with Diffuse Large B-cell Lymphoma

Abstract: The biology and clinical impact of bone marrow (BM) infiltration in patients with diffuse large B-cell lymphoma (DLBCL) remains unclear in the rituximab era. We retrospectively analyzed 232 patients diagnosed with DLBCL at our center between 1999 and 2014. Concordant-presence of large cells similar to those of the lymph node biopsy- and discordant-infiltration by small cells forming lymphoid aggregates, lacking cytological atypia-BM infiltration was defined by histological criteria and further characterized by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 33 publications
2
15
0
Order By: Relevance
“…Compared with previous studies, the study similarly found that the clinical characteristics of concordant mBMI were associated with poor ECOG performance status, high-intermediate standard, and NCCN-IPI risks, compared with the discordant morphologic marrow involvements. 37 38 39 Complete response (CR) was achieved in all three patients with discordant mBMI, however, half of patients with concordant mBMI failed to achieve a CR after R-CHOP chemotherapy. All three patients with discordant atypical morphology or focal marrow invasion had IgH rearrangement.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with previous studies, the study similarly found that the clinical characteristics of concordant mBMI were associated with poor ECOG performance status, high-intermediate standard, and NCCN-IPI risks, compared with the discordant morphologic marrow involvements. 37 38 39 Complete response (CR) was achieved in all three patients with discordant mBMI, however, half of patients with concordant mBMI failed to achieve a CR after R-CHOP chemotherapy. All three patients with discordant atypical morphology or focal marrow invasion had IgH rearrangement.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, one of the conceivable limitations in this study is the lack of consideration for or observation of concordant BM disease defined by the involved BM area consisting of mostly large noncleaved lymphoma cells and discordant BM disease defined by the involved BM consisting of mostly small low-grade lymphoma cells in DLBCL [ 36 , 37 , 38 ]. It has been reported that the subclassification of invaded lymphoma cells into two morphologically distinct types, i.e., concordant and discordant types, is associated with prognosis [ 36 , 37 , 38 ]. However, we could not evaluate this point because pathologists reported no discordant BM involvement with BM biopsy or BM clot assessment in our study.…”
Section: Discussionmentioning
confidence: 99%
“…However, we could not evaluate this point because pathologists reported no discordant BM involvement with BM biopsy or BM clot assessment in our study. Considering discordant clonal lymphoid cells occasionally reflects the incidental co-occurrence of indolent clonal lymphoid proliferation with DLBCL [ 36 , 37 ], one of the conceivable reasons which underlay the discrepancy between frequent discordant BM involvement in previous reports and the absence of discordant BM disease in our cohort may be the distinct racial impact on the frequency of indolent B cell neoplasms, such as follicular lymphoma, chronic lymphoid leukemia (CLL) and its precursor, monoclonal B-cell lymphocytosis (MBL). For instance, the incidence of CLL was about 5–10 folds less in Asians than in Caucasians [ 39 , 40 ], and this was also the case with MBL [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…BMinv is a common occurrence in lymphoma. A recent study [ 19 ] revealed that patients with BMinv in DLBCL had a higher risk of central nervous system recurrence and a lower progression-free survival; therefore, timely and accurate diagnosis of lymphoma BMinv is important for disease staging, choosing treatment options, and evaluating the prognosis. Current methods for clinical evaluation of BMinv in lymphoma include BMB, PET/CT, and whole-body MRI [ 11 , 20 ].…”
Section: Discussionmentioning
confidence: 99%